2017
DOI: 10.1073/pnas.1703205114
|View full text |Cite
|
Sign up to set email alerts
|

Development of an optimized synthetic Notch receptor as an in vivo cell–cell contact sensor

Abstract: Detection and manipulation of direct cell-cell contact in complex tissues is a fundamental and challenging problem in many biological studies. Here, we report an optimized Notch-based synthetic receptor (synNQ) useful to study direct cell-cell interactions in Drosophila. With the synNQ system, cells expressing a synthetic receptor, which contains Notch activation machinery and a downstream transcriptional activator, QF, are activated by a synthetic GFP ligand expressed by contacting neighbor cells. To avoid ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…For example, the extracellular ligand-binding domains and the intracellular effector domains of Notch can both be replaced with engineered alternative domains to create synthetic receptors that sense arbitrary inputs and activate arbitrary target genes . These and related synthetic communication systems have been used for controlling immune cell responses , engineering synthetic multicellular patterns (Toda et al, 2018) and mapping direct cell-cell contact and neural connections (He et al, 2017;Huang et al, 2016Huang et al, , 2017. By demonstrating the possibility of orthogonal multiplexing, they provoke the question, which we address in the section 'Sensing ligand combinations': why do so many natural pathways appear to use many-to-many ligandreceptor specificities?…”
Section: Modulating or Programming Ligand Specificitymentioning
confidence: 99%
“…For example, the extracellular ligand-binding domains and the intracellular effector domains of Notch can both be replaced with engineered alternative domains to create synthetic receptors that sense arbitrary inputs and activate arbitrary target genes . These and related synthetic communication systems have been used for controlling immune cell responses , engineering synthetic multicellular patterns (Toda et al, 2018) and mapping direct cell-cell contact and neural connections (He et al, 2017;Huang et al, 2016Huang et al, , 2017. By demonstrating the possibility of orthogonal multiplexing, they provoke the question, which we address in the section 'Sensing ligand combinations': why do so many natural pathways appear to use many-to-many ligandreceptor specificities?…”
Section: Modulating or Programming Ligand Specificitymentioning
confidence: 99%
“…SynNotch receptors have also been used in the field of developmental biology to ask more basic questions. Two studies (He et al, 2017;Huang et al, 2016) reported that optimized SynNotch receptors can indeed be activated by direct cell-cell contact in vivo in Drosophila. Both studies used the SynNotch system to reveal such direct cell interactions using binary expression systems to express the ligand (GFP) in one subset of cells, while expressing the SynNotch receptor (harbouring a GFP nanobody and an intracellular transcription activation domain) in another subset of cells (He et al, 2017;Huang et al, 2016).…”
Section: Synergies Between Developmental Biology and Synthetic Biologymentioning
confidence: 99%
“…Two studies (He et al, 2017;Huang et al, 2016) reported that optimized SynNotch receptors can indeed be activated by direct cell-cell contact in vivo in Drosophila. Both studies used the SynNotch system to reveal such direct cell interactions using binary expression systems to express the ligand (GFP) in one subset of cells, while expressing the SynNotch receptor (harbouring a GFP nanobody and an intracellular transcription activation domain) in another subset of cells (He et al, 2017;Huang et al, 2016). Depending on the downstream response of the SynNotch receptor, this setup can reveal cell-cell contacts by inducing a detectable response in the interacting cells (such as the expression of a fluorescent protein; He et al, 2017;Huang et al, 2016) or can act as a synthetic signalling system that induces the expression of a POI (Huang et al, 2016).…”
Section: Synergies Between Developmental Biology and Synthetic Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic Notch (synNotch) receptor is a recently developed cell-cell contact sensing platform, which contains a customized extracellular sensor module, a transmembrane core domain of native Notch, and a customized intracellular responder module (Morsut et al, 2016). Because of its extraordinary flexibility in terms of customizable sensing/response behaviors, the synNotch receptor serves as a powerful tool for cell engineering (Roybal et al, 2016a;Roybal et al, 2016b;He et al, 2017). In the current study, we combined the synNotch receptor with the CRISPR/Cas9 system to develop a cell-cell interaction inducible gene regulated tool.…”
mentioning
confidence: 99%